Impact of Positive Reinforcement in Guided Inquiry Learning Model Based on Behavioristic Theory on Science Learning Outcomes Grade 5 - Putri Budiastini, Ni Putu; Suarni, Ni Ketut; Margunayasa, i Gede (Psikostudia : Jurnal Psikologi, 2023)
The importance of research on the impact of positive reinforcement in behavioristic theory-based guided inquiry learning models on grade 5 science learning outcomes lies in the need to understand the effectiveness of the latest learning methods. This allows for a deeper understanding of the most efficient ways to improve students' understanding of the natural sciences at the primary school level. The results of the analysis showed the superiority of Natural Science (Science) learning outcomes in the group of students who participated in guided inquiry learning based on behavioristic theory withteori behavioristiks compared to the control group who received conventional learning. The average score of the experimental group (21.80) was significantly higher than that of the control group (18), confirming the significant difference between the two. Factors such as active involvement of students in independent exploration, the use ofteori behavioristiks as learning media, students' ability to solve problems, and group discussions are key in the advantages of behavioristic-based guided inquiry models in increasing understanding of science concepts at the elementary school level. This finding is in line with previous research, confirming that a guided inquiry approach with the use ofteori behavioristik and behavioristic principles has a significant positive impact in improving science learning outcomes in grade V students.Pentingnya penelitian tentang dampak penguatan positif dalam model pembelajaran inkuiri terbimbing berbasis teori behavioristik terhadap hasil belajar IPA kelas 5 terletak pada kebutuhan akan pemahaman efektivitas metode pembelajaran terkini. Hal ini memungkinkan pemahaman lebih dalam terhadap cara yang paling efisien dalam meningkatkan pemahaman siswa terhadap ilmu pengetahuan alam pada tingkat sekolah dasar. Hasil analisis menunjukkan keunggulan hasil belajar Ilmu Pengetahuan Alam (IPA) pada kelompok siswa yang mengikuti pembelajaran inkuiri terbimbing berbasis teori behavioristik dibandingkan kelompok kontrol yang menerima pembelajaran konvensional. Skor rata-rata kelompok eksperimen (21,80) secara signifikan lebih tinggi dibandingkan kelompok kontrol (18), menegaskan perbedaan yang signifikan antara keduanya. Faktor-faktor seperti keterlibatan aktif siswa dalam eksplorasi mandiri, penggunaanteori behavioristik sebagai media pembelajaran, kemampuan siswa dalam memecahkan masalah, serta diskusi kelompok menjadi kunci dalam keunggulan model inkuiri terbimbing berbasis behavioristik dalam meningkatkan pemahaman konsep IPA di tingkat sekolah dasar. Temuan ini sejalan dengan penelitian terdahulu, menegaskan bahwa pendekatan inkuiri terbimbing dengan pemanfaatanteori behavioristik dan prinsip-prinsip behavioristik memberikan dampak positif yang signifikan dalam meningkatkan hasil belajar IPA pada siswa kelas V.